2002
DOI: 10.1016/s1097-2765(02)00572-5
|View full text |Cite
|
Sign up to set email alerts
|

Loss of the Muscle-Specific Chloride Channel in Type 1 Myotonic Dystrophy Due to Misregulated Alternative Splicing

Abstract: Myotonic dystrophy type 1 (DM1) is a dominant multisystemic disorder caused by a CTG expansion in the 3' untranslated region of the DMPK gene. A predominant characteristic of DM1 is myotonia resulting from skeletal muscle membrane hyperexcitability. Here we demonstrate loss of the muscle-specific chloride channel (ClC-1) mRNA and protein in DM1 skeletal muscle tissue due to aberrant splicing of the ClC-1 pre-mRNA. The splicing regulator, CUG binding protein (CUG-BP), which is elevated in DM1 striated muscle, b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

25
456
2
10

Year Published

2003
2003
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 549 publications
(493 citation statements)
references
References 55 publications
25
456
2
10
Order By: Relevance
“…Furthermore, we performed RT-PCR for Clcn1 and Tnnt3 in our mice and uncovered splicing abnormalities (Fig. 2c) similar to those in transgenic mice overexpressing CUG repeats 15 , in the Mbnl1ΔE3 knockout mouse 16 and in individuals with myotonic dystrophy [14][15][16] . Skeletal muscle histology also showed induction of central nuclei, nuclear clumping and fiber size variation as seen in individuals with DM1 (Fig.…”
mentioning
confidence: 62%
See 2 more Smart Citations
“…Furthermore, we performed RT-PCR for Clcn1 and Tnnt3 in our mice and uncovered splicing abnormalities (Fig. 2c) similar to those in transgenic mice overexpressing CUG repeats 15 , in the Mbnl1ΔE3 knockout mouse 16 and in individuals with myotonic dystrophy [14][15][16] . Skeletal muscle histology also showed induction of central nuclei, nuclear clumping and fiber size variation as seen in individuals with DM1 (Fig.…”
mentioning
confidence: 62%
“…The cardiac conduction abnormalities observed in these mice are exactly like those seen in up to 70% of individuals with DM1: namely, heart block and atrioventricular node dysfunction 13 . This is the first transgenic mouse model with cardiac conduction Myotonia in DM1 and DM2 is associated with reduced chloride channel (Clcn1, also known as Clc-1) expression and splicing abnormalities of Clcn1 mRNA 14,15 . We found ClC-1 protein significantly reduced or absent from the muscle membranes in mice in which transgene expression was induced (Fig.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Aberrant processing of mRNAs in tumor cells has been described for the MDM2, RasGRP4, SLP-65, TLE1, TLE4, MTA1 and CD44 genes and is emerging as an important characteristic of tumor cells (Bartel et al, 2002;Kumar et al, 2002;Reuther et al, 2002;Yang et al, 2002;Jumaa et al, 2003;Venables, 2004;Watermann et al, 2006) and is observed in other diseases, such as myotonic dystrophy (Charlet-B et al, 2002). In aberrant splicing, portions of exons, portions of introns or both are retained within transcripts that fail to be purged by the cellular pathways designed to scavenge abnormal mRNAs, such as nonsense-mediated decay (Culbertson, 1999;Wilkinson and Shyu, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…A multi-step model for DM1 pathogenesis has been proposed [reviewed in reference 2]: (1) the mutant gene is transcribed, giving rise to transcripts that contain an expanded CUG repeat (CUG exp ) [3]; (2) the CUG exp transcripts accumulate in RNA nuclear (ribonuclear) foci [4]; (3) RNA binding proteins, including muscleblind 1 (MBNL1), are sequestered in the ribonuclear foci [5,6]; (4) altered activity of splicing factors, such as MBNL1 and CUG binding protein 1, leads to abnormal alternative splicing for a sub-group of pre-mRNAs [7,8]; and (5) expression of inappropriate splice products leads to symptoms of DM1. For example, CUG exp RNA triggers abnormal alternative splicing of the ClC-1 chloride channel, and the predominant ClC-1 splice products expressed in DM1 muscle are devoid of ion channel activity [9][10][11]. Deficiency of ClC-1 channels contributes to myotonia in DM1, and can be reversed in a transgenic mouse model by overexpressing MBNL1 to levels that exceed the capacity of CUG exp RNA to sequester proteins [12].…”
Section: Introductionmentioning
confidence: 99%